AN ANALYSIS SEMIOTICS SING OF REWIND INDONESIA 2021 VIDEO POSTER - Putri, I Gusti Ayu Vina Widiadnya; Putri, Ni Putu Belina (Uniqbu Journal of Social Sciences, 2022)
The purpose of this study is to analyze the meaning of visual illustration signs on the video poster “Rewind Indonesia 2021” using Ferdinand de Saussure’s semiotic theory. This study uses a qualitative research method to describe the signs behind the form video poster “Rewind Indonesia 2021” that was initiated by Chandra Liow, Aulion, Jovial da Lopez, Natya Shina, Rendy Pritananda and Ferry Irwandi. The discovery of information through the project is accomplished by digging up the information offered in a project in order to comprehend the conditions or context of what is actually occurring in it. The following is an analysis of the components in the semiotics of signs and markers through the poster work of Rewind Indonesia 2021 so that an analysis of verbal and nonverbal signs is carried out using Saussure’s theory of signifier and signified.